(untitled) (Balneo and PRM Research Journal, 2022)
Background: Static and dynamic balance are factors of major importance in the manifestation of human motor skills at a higher level. Purpose: The determination of variations in the performance of balance tests for young women students at the Faculty of Physical Education and Sports (48 cases in the 1st year of bachelor’s degree), divided and analyzed 3 BMI levels (underweight / 7 cases, normal weight / 34 cases and overweight / 7 cases ) and comparing these results with other similar research. Material and method: The testing of the group was scheduled at the Research Center for Human Performance, belonging to the Faculty of Physical Education and Sports in Galați, in the month of April of the 2018-2019 academic year. For the assessment of balance, 7 tests were used, of which 4 associated with dynamic postural stability (Walk and turn field sobriety test / errors, Functional reach test / cm, Fukuda test / degrees of rotation, Bass test / points) and 3 measuring static stability (Flamingo test / falls, One leg standing with eyes closed / sec, Stork test / sec). Nonparametric tests (Mann-Whitney U) were applied to compare differences between batches. Results: The average values of underweight and normal-weight women are better than those of overweight women for the entire set of assessment tests. The underweight group has the best results for the Standing balance test, Functional reach test, Flamingo test, Walk and turn field sobriety test, Fukuda test, and the normal weight women for Stork test, respectively Bass test. We found the lack of significant thresholds when comparing the results between the 3 groups (P> 0.05) for Stork test, Standing balance test and Functional reach test, so the working hypothesis formulated is only partially confirmed. The only significant difference between underweight and normal weight (P <0.05) is found in the Flamingo test, with better values for underweight. Significant difference thresholds for Flamingo test and Fukuda test are recorded between the underweight and overweight groups (Z values have associated thresholds P<0.05). The most significant differences are found between the normal weight and overweight groups (P <0.05), respectively for the Bass test, Fukuda test and Walk and turn field sobriety test. Conclusion: Constant physical activity (as a feature of the analyzed group) reduces the chances of significant differences in all balance tests between BMI levels.